Public health services and their relationship with rapid HIV test utilization and access for key populations in Morelos, Mexico - Carlos Jesús Conde González; Silvia Magali Cuadra-Hernández; Jesús Israel Bernabé-Aranda; Mario Salvador Sánchez-Domínguez; Doris Verónica Ortega-Altamirano (Instituto Nacional de Salud Pública, 2015)
Objective. In 2009, 4 749 rapid HIV tests were run in Morelos, Mexico, despite lacking evidence on their results. This article seeks to analyze how public health organization relates to utility of rapid HIV test among healthcare users. Materials and methods. Joint study: comparison of differences in applied test and positive results for each group with the Bonferroni statistical tool, observational study in 34 health subsystems, and 11 interviews with public healthcare users. Results. Each subsystem processes influenced the use and usefulness of screening; for instance, primary care centers test only pregnant women and exclude men who have sex with men (MSM). That group shows significant differences (p<0.007) in the HIV-positive test with respect to other groups. Conclusions. Despite the availability of rapid detection tests and epidemiological evidence, the way public health services are organized impedes an efficient diagnosis in the group with higher risk, namely MSM. The distribution of rapid HIV tests was guided by stigmatization.